Characterisation of human antibody responses to Chikungunya virus infection / Chua Chong Long - Chua , Chong Long (2017)
Chikungunya virus (CHIKV), an alphavirus of the family Togaviridae, causes fever, rash and joint pain. There are three CHIKV genotypes: West African, Asian and East/Central/South African (ECSA). The latter two genotypes have been co-circulating and causing outbreaks in Malaysia. Although vaccines are still under development, a greater understanding of the human antibody responses to CHIKV infection is essential. The overall aim of the present study was to characterise human antibody responses to CHIKV. The antibody responses were studied in 102 serum samples collected during CHIKV outbreaks in Malaysia. The first objective of the study was to develop a panel of monoclonal antibodies targeting CHIKV E2 glycoprotein as immunological tools. The monoclonal antibody clone B-D2(C4) was chosen for use in subsequent serum neutralisation assay and development of immunoassays. For the second objective, the characteristics of cross-genotype immunity and epitopes were investigated. The neutralising capacity of late convalescent sera (ECSA and Asian) was analysed against representative clinical isolates as well as viruses rescued from infectious clones of ECSA and Asian CHIKV. Using whole virus antigen and recombinant E1 and E2 envelope glycoproteins, the antibody binding sites, epitopes and antibody titres were investigated using ELISA and western blotting. Both ECSA and Asian sera demonstrated stronger neutralising capacity against ECSA genotype, which corresponds to stronger epitope-antibody interaction. ECSA serum targeted conformational epitope sites in the E1-E2 glycoprotein, while E1-E211K, E2-I2T, E2-H5N, E2-G118S and E2- S194G were the key amino acids that enhanced cross-neutralising efficacy. As for Asian serum, the antibodies targeting E2 glycoprotein correlated with neutralising efficacy and I2T, H5N, G118S and S194G altered and improved the neutralisation efficacy. For the third objective, the pathogenic role of antibodies from immune sera was explored. Evidence for CHIKV antibody-dependent enhancement (ADE) was demonstrated in iv K562 leukaemia cells, which express the Fc gamma receptor FcɣRIIA (CD32) and supports active virus production. For the fourth objective, the neutralising role of IgM at different times post-infection was described and the independent contributions of IgM and IgG towards the neutralising capacity of human immune sera were examined. The differences in neutralising epitopes of IgM and IgG were investigated as well. Neutralising IgM starts to appear as early as day 4 of symptoms, and their appearance from day 6 is associated with a reduction in viraemia. IgM acts in a complementary manner with early IgG, but plays the main neutralising role up to a point between days 4 and 10 which varies between individuals. After this point, total neutralising capacity is attributable almost entirely to the robust neutralising IgG response. IgM preferentially binds and targets epitopes on the CHIKV surface E1-E2 glycoproteins, rather than individual E1 or E2. Overall, the findings from this study provide new knowledge in the immunoprotection mechanisms against co-circulating CHIKV genotypes. The findings have implications for effective design and development of vaccines, human monoclonal antibodies and diagnostic serological assays.